Interpopulation variability and adaptive potential for reduced glyphosate sensitivity in Alopecurus myosuroides. (10th August 2017) - Davies, L R; Neve, P
Summary: Glyphosate use in the United Kingdom has more than doubled in the last 20 years. Much of this increase is driven by efforts to control herbicide resistant weeds, particularly Alopecurus myosuroides, prior to crop drilling. There is precedent for evolution of glyphosate resistance in similar situations, raising concerns over the sustainability of glyphosate use in the UK. We used dose–response experiments to examine variation in glyphosate sensitivity amongst 40 field‐collected A. myosuroides populations. No populations were resistant to glyphosate, but ED90 values ranged between 354 and 610 g a.i. ha −1 . Five populations had ED90 values significantly higher than the unexposed control population collected from a site at Rothamsted Research with no previous glyphosate exposure. Recurrent selection experiments were performed to determine whether variation in glyphosate sensitivity had a heritable basis. Following two rounds of selection, five of six field populations evolved significantly reduced sensitivity to glyphosate, with R/S ratios, based on estimated ED50 values, ranging from 1.2 to 1.5. These results confirm that there is a heritable basis to variation in glyphosate sensitivity. The response to selection was modest. Evolved populations were not highly resistant to glyphosate, although some twice‐selected individuals survived recommended field rates. These results do not represent definitive proof of the potential of A. myosuroides to evolve glyphosate resistance, although they do indicate caution is needed when considering the sustainability of increased glyphosate use to control this herbicide resistance‐prone species.